2000
DOI: 10.1002/1097-4687(200011)246:2<53::aid-jmor1>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic squeezing of sperm bundles at the late stage of spermatogenesis in the silkworm,Bombyx mori

Abstract: Silkworm (Lepidoptera) males produce dimorphic sperm, nucleate eupyrene sperm, and anucleate apyrene sperm. The eupyrene sperm is the ordinary sperm fertilizing eggs, while the function of the apyrene sperm, which are about four times as numerous as the eupyrene sperm, is still uncertain. We found the peristaltic phenomenon at the very late stage of spermatogenesis. Peristalsis occurs in both eupyrene and apyrene sperm bundles. Through peristaltic action, cytoplasm of the eupyrene sperm and both cytoplasm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…We confirm that the apyrene sperm are indispensable in fertilisation of the silkworm and polyploid apyrene sperm function as a substitute for the diploid (Table 1). The irregular meiosis and loss of the nuclei by peristaltic squeezing are common in apyrene spermatogenesis of any ploidy (Wolf & Bastmeyer, 1991;Kawamura et al, 2000Kawamura et al, , 2001. In B. mori, however, there are phenomena which do not always coincide with the proposed function of the apyrene sperm in Lepidoptera (see Introduction): (1) the presence of apyrene sperm in the bursa copulatrix does not delay female remating, (2) the spermatophore is not a requisite structure for dissociation of eupyrene sperm bundles but motility of apyrene sperm may promote the dissociation of eupyrene sperm bundles without the spermatophore in the bursa copulatrix, (3) eupyrene sperm bundles crossed the basement membrane of a testis without apyrene sperm, (4) if apyrene sperm only provided nutrients for the eupyrene sperm, then a single copulation by DH males would fertilise eggs.…”
Section: Discussionmentioning
confidence: 99%
“…We confirm that the apyrene sperm are indispensable in fertilisation of the silkworm and polyploid apyrene sperm function as a substitute for the diploid (Table 1). The irregular meiosis and loss of the nuclei by peristaltic squeezing are common in apyrene spermatogenesis of any ploidy (Wolf & Bastmeyer, 1991;Kawamura et al, 2000Kawamura et al, , 2001. In B. mori, however, there are phenomena which do not always coincide with the proposed function of the apyrene sperm in Lepidoptera (see Introduction): (1) the presence of apyrene sperm in the bursa copulatrix does not delay female remating, (2) the spermatophore is not a requisite structure for dissociation of eupyrene sperm bundles but motility of apyrene sperm may promote the dissociation of eupyrene sperm bundles without the spermatophore in the bursa copulatrix, (3) eupyrene sperm bundles crossed the basement membrane of a testis without apyrene sperm, (4) if apyrene sperm only provided nutrients for the eupyrene sperm, then a single copulation by DH males would fertilise eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Kawamura et al (2000) observed the developmental process of parasperm by using cultured sperm bundles enclosing 256 sperm cells. They termed this process "peristaltic squeezing," which starts from the anterior end of the sperm bundle at the fi nal stage of spermiogenesis of both types of sperm ( Fig.…”
Section: Parasperm Of Invertebratesmentioning
confidence: 99%
“…However, the nuclei of the apyrene sperm are squeezed out together with the cytoplasmic debris. This peristaltic squeezing of sperm bundles in the silkworm is thought to be the fi nal control mechanism forming eupyrene sperm and apyrene parasperm (Kawamura et al, 2000(Kawamura et al, , 2001.…”
Section: Parasperm Of Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in detail previously (Yamashiki & Kawamura, 1997;Kawamura et al, 2000), spermatocysts and sperm bundles from excised testes of fifth-instar larvae and pupae were smeared on a coverslip coated with 3-aminopropyl-triethoxy-silane (Sigma Chemical, St. Louis, MO) and fixed in 4% paraformaldehyde in phosphate-buffered saline (PBS, pH 7.0) for 1 h. Mouse monoclonal antibody against chicken alpha-tubulin (Cederlane Laboratory, Hornby, Ontario, Canada), which is cross-hybridised with Bombyx alpha-tubulin, and fluorescein isocyanate-conjugated goat antimouse IgG (MBL, Tokyo, Japan) with propidium iodide (Sigma) was applied on the coverslip. The coverslip was mounted on a glass slide with 90% glycerin-DABCO (Sigma) mountant.…”
Section: Indirect Immunofluorescence Staining For Tubulinmentioning
confidence: 99%